From megaprojects to tourism gentrification? The case of Santa Cruz Verde 2030 (Canary Islands, Spain) - Marcus Hübscher (Boletín de la Asociación de Geógrafos Españoles, 2019)
The inner-city oil refinery in Santa Cruz de Tenerife, Spain, has been shaping the city’s urbanism as an employer, but also as a polluter and a physical barrier for more than 80 years. The megaproject Santa Cruz Verde 2030 aims at transforming this area into a mixed-use urban quarter. Based on a mixed methods approach, this paper analyses the impacts of the megaproject by means of document, spatial and statistical analyses. The project is estimated to increase the city’s green areas by 39 % and the number of hotel beds by 70 %, provoking a strong touristifaction. Santa Cruz Verde 2030 stands for a new type of megaprojects, offering a variety of uses and sustainability wordings. Nevertheless, the impacts might reconfigure the city’s urbanism as a whole, shifting centralities to its southwest. On a neighbourhood level, spillover effects are expected to have diverging consequences. While in the Los Llanos neighbourhood gentrification and tourism are fostered, in Buenos Aires the megaproject implies the opportunity to integrate this currently segregated quarter into the city. Against this background, the paper outlines the necessity of transparent planning and monitoring processes, in order to ensure the sustainability of this new urban quarter.